Minimally Invasive Pronator Quadratus Sparing Approach versus Extended Flexor Carpi Radialis Approach with Pronator Quadratus Repair for Volar Plating in Distal Radial Fractures - Goorens, Chul ki; Debaenst, Niels; Van Royen, Kjell; Provyn, Steven; Goubau, Jean F. (Journal of Wrist Surgery, 2021)
Background Several volar plating techniques exist to treat distal radial fractures.Question We investigated minimally invasive plate osteosynthesis (MIPO) with pronator quadratus (PQ) sparing versus conventional flexor carpi radialis approach for volar plating with PQ repair after distal radial fractures during the first postoperative year.Patients and Methods Prospective data of two consecutive cohorts were compared: 62 patients in MIPO group with an average age of 61.2 years and 66 patients in PQ repair group with an average age of 61.4 years completed the entire follow-up period.Results Range of motion was not significantly different, except flexion–extension that was significantly higher in the MIPO group. Quick Disabilities of the Arm, Shoulder and Hand was significantly lower in the MIPO group. Pain visual analogue scale was only significantly lower at 6 weeks. Grip strength measurements and patient satisfaction were not significantly different.Conclusions MIPO volar plating with PQ sparing is a surgical technique that can be chosen according to surgeon's preference and expertise, resulting in a better flexion–extension mobility and function score according to our study.Level of evidence This is a Level 3 study.
Keywords: minimally invasive; MIPO; distal radius; pronator quadratus; repair; sparing; volar plating